Application of intellectual technologies for optimization of the structure of controlled technological systems - V. S. Smorodin; V. A. Prokhorenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
A research direction in the field of controllable technological systems based on construction of artificial neural network models for functioning of intellectual real-time decision support systems is proposed.